Prognostic value of neutrophil/lymphocyte racio in palliative non-small cell lung cancer patients treated with imunotherapy - Romão, Raquel (2024)
Introduction: Immune checkpoint inhibitors (IC) are a new therapeutic option for non-small cell lung cancer. A higher neutrophil/lymphocyte ratio has been associated with worse outcomes in patients treated with immune checkpoint inhibitors, lung cancer included. Aim: Study the relation between value of neutrophil/lymphocyte ratio at day one (D1) and day 30 (D30) of treatment, and overall survival (OS) and progression free survival (PFS) in metastized non -small cell lung cancer patients treated with pembrolizumab, nivolumab or atezolizumab. Material and methods: It were performed a retrospective chart review including all patients with metastized non-small cell lung cancer diagnosed and treated with IC, between July 2016 and January 2020 in Centro Hospitalar Universitario of Porto. Demographic, clinic and treatment data were extracted. Relation between rNL ≥5 at D1 and D30 and OS and PFS was analyzed. Results: 79 patients were identified, median age of 64,5 years old (range 32-84), most of them of male gender (n=61; 77,2%), with smoking habits (n=66; 83,5%) and multiple comorbidities (Charlson Index median of 8). Adenocarcinoma was the most frequent histologic type (n=55, 69,6%) and 51 (60,8%) patients had stage IV disease at diagnosis. Pembrolizumab (n=44, 55,7%) was the most used IC, followed by nivolumab (n=29; 36,7%) and atezolizumab (n=6; 7,6%), predominantly used in second line of treatment (60,8%). In this group study there was a relation between rNL and OS. Median follow up time was 4 months. The rNL ≥5 at D1 had no impact in PFS (rNL<5 4,4m; rNL≥5 2,92m – p 0,792) and OS (rNL<5 9,10m; rNL≥5 4,30m – p 0,260). The rNL≥5 at D30 had no impact on PFS (rNL<5 4,93m; rNL≥5 2,43m – p 0,066) but had on OS (rNL<5 10,5m; rNL≥5 3,93m – p 0,046). Discussion/Conclusion: The results corroborate the negative prognostic impact of a high rNL at D30 on survival of the patients included. Although there was no significative difference in the rest of the analysis, a tendency of this impact has been verified. As limitations of this study, we had the retrospective character, the heterogeneity of the sample and the duration of follow up. The prospective confirmation of this findings could introduce a new element to select patients who will benefit of IC treatment, of easy applicability in clinical practice.